Design Of Electronic Perinatal Death Certificate Form At Dr.Soedomo Trenggalek Regional Hospital In 2024 - Adiesviony Piky Arini Putri; Retno Dewi Prisusanti; Isti Komah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2024)
Recording death certificates involves documenting various diseases or conditions that lead to a series of deaths, accidents, injuries, and death. RSUD dr. perinatal age, but also the quality of statistical reporting of perinatal infant deaths in hospitals. The aim of carrying out this research is to produce a special electronic-based perinatal death certificate form format at Dr. Soedomo Trenggalek Regional Hospital which can provide a more complete picture regarding the identity of the baby, the baby's mother, diagnosis and other items provided by the doctor in order to increase the accuracy of recording. death at perinatal age. This research method is a qualitative type using data collection techniques in the form of observation, interviews, documentation and brainstorming by exploring 3 variables in the form of physical aspects, anatomical aspects and content aspects. Based on the research results, it can be concluded that the design of the general death certificate at Dr. Soedomo Trenggalek still does not contain more detailed information regarding the baby's condition before death so that it can cause errors in determining UCOD (Underlying Cause of Death) according to ICD 10. Therefore, the preparation of this special perinatal death certificate has three main aspects, namely the physical aspect, the anatomy, and content aspects according to user filling needs. In its implementation, the design of this perinatal death form will be designed electronically so that the information contained in it will be integrated electronically through the hospital's SIMRS to support the transition period towards RME (Electronic Medical Records).